2019
DOI: 10.3389/fphar.2019.01226
|View full text |Cite
|
Sign up to set email alerts
|

Danshen Improves Survival of Patients With Breast Cancer and Dihydroisotanshinone I Induces Ferroptosis and Apoptosis of Breast Cancer Cells

Abstract: Danshen (salvia miltiorrhiza Bunge) is widely used in traditional Chinese medicine. However, it is definite clinical effort and mechanism on breast cancer is unclear. In our study, we used the real-world database to investigate in vivo protective effort of danshen in the breast cancer patients through using population-based data from the Taiwan National Health Insurance Research Database (NHIRD). In vitro, human breast cancer cells (MCF-7 cells and MDA-MB-231 cells) were used to investigate the effect and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 40 publications
1
50
0
Order By: Relevance
“…A previous study indicated that tanshen induced ferroptosis in breast cancer cells, and significantly reduced the final tumor volume in a xenograft nude mouse model without adverse effects (31). Therefore, the present study aimed to evaluate the effects of DHI on the proliferation of glioma cells and investigate the contribution of ferroptosis to the underlying mechanism.…”
Section: Introductionmentioning
confidence: 93%
“…A previous study indicated that tanshen induced ferroptosis in breast cancer cells, and significantly reduced the final tumor volume in a xenograft nude mouse model without adverse effects (31). Therefore, the present study aimed to evaluate the effects of DHI on the proliferation of glioma cells and investigate the contribution of ferroptosis to the underlying mechanism.…”
Section: Introductionmentioning
confidence: 93%
“…Long non-coding RNAs (LncRNAs) have important roles in ferroptosis. For instance, lncRNA GABPB1-AS1 can down-regulate the GABPB1 level and inhibit its Zhang, K et al [84] Inhibit the expression of TFR1 Reduce the accumulation of Glu Decrease the depletion of Glu antioxidant capacity, thereby inducing ferroptosis in hepatic cancer cells [77].…”
Section: Ferroptosis and Hepatocellular Cancermentioning
confidence: 99%
“…Another study reported that the down-regulation of lncRNA P53RRA promoted ferroptosis by sequestering p53 in the nucleus [83]. In addition, as a herb widely used in traditional Chinese medicine, danshen has been reported to improve the prognosis of breast cancer, which may be due to the effects of its bioactive compound, dihydroisotanshinone I, in repressing the protein GPX4 expression and inducing ferroptosis [84].…”
Section: Ferroptosis and Breast Cancermentioning
confidence: 99%
“…demonstrated that Danshen, a traditional Chinese medicine, prolonged survival of patients with breast cancer by inducing cell ferroptosis [25]. Similarly, a study published in 2018 reported that natural compounds exerted antitumor activity through the induction of non-apoptotic programmed cell death, including ferroptosis [26], which provided an effective therapeutic strategy for patients with cancer.…”
Section: Introductionmentioning
confidence: 97%